Detectability of CO2 flux signals by a space‐based lidar mission. Issue 5 (11th March 2015) - Hammerling, Dorit M.; Kawa, S. Randolph; Schaefer, Kevin; Doney, Scott; Michalak, Anna M.
Abstract: Satellite observations of carbon dioxide (CO2 ) offer novel and distinctive opportunities for improving our quantitative understanding of the carbon cycle. Prospective observations include those from space‐based lidar such as the active sensing of CO2 emissions over nights, days, and seasons (ASCENDS) mission. Here we explore the ability of such a mission to detect regional changes in CO2 fluxes. We investigate these using three prototypical case studies, namely, the thawing of permafrost in the northern high latitudes, the shifting of fossil fuel emissions from Europe to China, and changes in the source/sink characteristics of the Southern Ocean. These three scenarios were used to design signal detection studies to investigate the ability to detect the unfolding of these scenarios compared to a baseline scenario. Results indicate that the ASCENDS mission could detect the types of signals investigated in this study, with the caveat that the study is based on some simplifying assumptions. The permafrost thawing flux perturbation is readily detectable at a high level of significance. The fossil fuel emission detectability is directly related to the strength of the signal and the level of measurement noise. For a nominal (lower) fossil fuel emission signal, only the idealized noise‐free instrument test case produces a clearly detectable signal, while experiments with more realistic noise levels capture the signal only in the higher (exaggerated) signal case. For the Southern Ocean scenario, differences due to the natural variability in the El Niño–Southern Oscillation climatic mode are primarily detectable as a zonal increase. Key Points: Detectability of regional changes in CO2 fluxes by space‐based lidar Permafrost thawing flux perturbation readily detectable by ASCENDS‐like mission Southern Ocean ENSO‐related flux variability detectable as zonal change